Integration of Islamic Religious Education Values in Physical Education, Sports, and Health Learning to Improve the Honesty Character of Elementary School Students - Aryanti Puspita Sari; Abdul Halik; Dadang Sumarna; St. Wardah Hanafieh Das (CV. Edujavare Publishing, 2026)
Honesty is a fundamental character value underlying the moral development of elementary school students. However, dishonest behaviors such as cheating, failing to admit mistakes, and unsportsmanlike conduct are still frequently observed in learning activities, including in Physical, Sport, and Health Education (PJOK). This study aims to describe the forms of integration of Islamic Religious Education (PAI) values into PJOK learning, to identify students' honesty character, and to analyze the contribution of this integration to strengthening students' honesty at SDN 003 Bontang Utara. A qualitative approach with a case study design was employed. Data were collected through observation, semi-structured interviews with the principal, the PAI teacher, the PJOK teacher, and students in grades III and V, as well as documentation studies, and were analyzed using the Miles, Huberman, and Saldana interactive model, consisting of data management, data reduction, data display, case analysis, and conclusion drawing and verification. Data validity was ensured through source triangulation, method triangulation, persistent observation, and prolonged engagement. The findings indicate that PAI values were systematically integrated through habitual prayer before and after lessons, teacher modeling, reinforcement of sportsmanship and fair play, and were supported by a religious school culture including congregational Dhuha prayer and Qur'an recitation. Students' honesty developed across six dimensions: honesty toward oneself, peers, teachers, parents, academic conduct, and toward Allah, although some students still experienced internal barriers such as fear and shame in admitting mistakes. The integration of PAI values into PJOK learning is shown to positively contribute to strengthening elementary students' honesty character, while also offering a collaborative and contextual integration model for character education grounded in Islamic values.